Question
upstudy study bank question image url

2. (a) \( \frac{1}{2}-\cos \left(\frac{\pi}{2}-\frac{1}{2} \arcsin \frac{3}{5}\right) \) (b) \( \sin \left(2 \arctan \frac{3}{4}\right)+\tan \left(\frac{1}{2} \arcsin \frac{5}{13}\right) \) (c) \( \tan \left(\frac{\pi}{4}+\frac{1}{2} \arccos \frac{a}{b}\right)+\tan \left(\frac{\pi}{4}-\frac{1}{2} \arccos \frac{a}{b}\right) \) (d) \( \cos \left(\arctan \frac{15}{8}-\arcsin \frac{7}{25}\right) \)

Ask by Phillips Smith. in Democratic Republic of the Congo
Feb 04,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

**Réponses aux problèmes :** 1. **(a)** \[ \frac{1}{2} - \cos\left(\frac{\pi}{2} - \frac{1}{2} \arcsin \frac{3}{5}\right) = \frac{5 - \sqrt{10}}{10} \] 2. **(b)** \[ \sin\left(2 \arctan \frac{3}{4}\right) + \tan\left(\frac{1}{2} \arcsin \frac{5}{13}\right) = \frac{29}{25} \] 3. **(c)** \[ \tan\left(\frac{\pi}{4} + \frac{1}{2} \arccos \frac{a}{b}\right) + \tan\left(\frac{\pi}{4} - \frac{1}{2} \arccos \frac{a}{b}\right) = \frac{2b}{a} \] 4. **(d)** \[ \cos\left(\arctan \frac{15}{8} - \arcsin \frac{7}{25}\right) = \frac{297}{425} \]

Solution

**Problème 2 :** Simplifions chacune des expressions données dans les parties (a) à (d). --- ### **(a)** \[ \frac{1}{2} - \cos\left(\frac{\pi}{2} - \frac{1}{2} \arcsin \frac{3}{5}\right) \] **Solution :** 1. **Soit** \(\theta = \arcsin\left(\frac{3}{5}\right)\). Ainsi, \(\sin \theta = \frac{3}{5}\) et, par le théorème de Pythagore, \(\cos \theta = \frac{4}{5}\). 2. **Utilisons l'identité trigonométrique :** \[ \cos\left(\frac{\pi}{2} - x\right) = \sin x \] Donc, \[ \cos\left(\frac{\pi}{2} - \frac{1}{2}\theta\right) = \sin\left(\frac{1}{2}\theta\right) \] 3. **Calculons \(\sin\left(\frac{1}{2}\theta\right)\) en utilisant la formule de la demi-angle :** \[ \sin\left(\frac{1}{2}\theta\right) = \sqrt{\frac{1 - \cos \theta}{2}} = \sqrt{\frac{1 - \frac{4}{5}}{2}} = \sqrt{\frac{1}{10}} = \frac{\sqrt{10}}{10} \] 4. **Substituons dans l'expression initiale :** \[ \frac{1}{2} - \frac{\sqrt{10}}{10} = \frac{5}{10} - \frac{\sqrt{10}}{10} = \frac{5 - \sqrt{10}}{10} \] **Réponse :** \[ \frac{5 - \sqrt{10}}{10} \] --- ### **(b)** \[ \sin\left(2 \arctan \frac{3}{4}\right) + \tan\left(\frac{1}{2} \arcsin \frac{5}{13}\right) \] **Solution :** 1. **Calculons \(\sin\left(2 \arctan \frac{3}{4}\right)\) :** - Soit \(\phi = \arctan\left(\frac{3}{4}\right)\), donc \(\tan \phi = \frac{3}{4}\). - Dans un triangle rectangle, les côtés opposé et adjacent sont respectivement 3 et 4, donc l'hypoténuse est 5. - Ainsi, \(\sin \phi = \frac{3}{5}\) et \(\cos \phi = \frac{4}{5}\). - Utilisons la formule de double angle : \[ \sin(2\phi) = 2 \sin \phi \cos \phi = 2 \times \frac{3}{5} \times \frac{4}{5} = \frac{24}{25} \] 2. **Calculons \(\tan\left(\frac{1}{2} \arcsin \frac{5}{13}\right)\) :** - Soit \(\theta = \arcsin\left(\frac{5}{13}\right)\), donc \(\sin \theta = \frac{5}{13}\) et \(\cos \theta = \frac{12}{13}\). - Utilisons la formule de la demi-angle pour la tangente : \[ \tan\left(\frac{\theta}{2}\right) = \frac{\sin \theta}{1 + \cos \theta} = \frac{\frac{5}{13}}{1 + \frac{12}{13}} = \frac{\frac{5}{13}}{\frac{25}{13}} = \frac{5}{25} = \frac{1}{5} \] 3. **Additionnons les deux résultats :** \[ \frac{24}{25} + \frac{1}{5} = \frac{24}{25} + \frac{5}{25} = \frac{29}{25} \] **Réponse :** \[ \frac{29}{25} \] --- ### **(c)** \[ \tan\left(\frac{\pi}{4} + \frac{1}{2} \arccos \frac{a}{b}\right) + \tan\left(\frac{\pi}{4} - \frac{1}{2} \arccos \frac{a}{b}\right) \] **Solution :** 1. **Soit** \(\theta = \frac{1}{2} \arccos\left(\frac{a}{b}\right)\). Nous souhaitons simplifier : \[ \tan\left(\frac{\pi}{4} + \theta\right) + \tan\left(\frac{\pi}{4} - \theta\right) \] 2. **Utilisons les formules de l'addition pour la tangente :** \[ \tan\left(\frac{\pi}{4} + \theta\right) = \frac{1 + \tan \theta}{1 - \tan \theta} \] \[ \tan\left(\frac{\pi}{4} - \theta\right) = \frac{1 - \tan \theta}{1 + \tan \theta} \] 3. **Additionnons les deux expressions :** \[ \frac{1 + \tan \theta}{1 - \tan \theta} + \frac{1 - \tan \theta}{1 + \tan \theta} = \frac{(1 + \tan \theta)^2 + (1 - \tan \theta)^2}{1 - \tan^2 \theta} \] \[ = \frac{1 + 2\tan \theta + \tan^2 \theta + 1 - 2\tan \theta + \tan^2 \theta}{1 - \tan^2 \theta} \] \[ = \frac{2 + 2\tan^2 \theta}{1 - \tan^2 \theta} = 2 \times \frac{1 + \tan^2 \theta}{1 - \tan^2 \theta} \] 4. **Simplifions en utilisant l'identité \(1 + \tan^2 \theta = \frac{1}{\cos^2 \theta}\) :** \[ 2 \times \frac{\frac{1}{\cos^2 \theta}}{1 - \tan^2 \theta} = 2 \times \frac{1}{\cos^2 \theta (1 - \tan^2 \theta)} \] \[ = 2 \times \frac{1}{\cos(2\theta)} \] 5. **Puisque \(2\theta = \arccos\left(\frac{a}{b}\right)\), nous avons :** \[ \cos(2\theta) = \frac{a}{b} \] \[ \Rightarrow 2 \times \frac{1}{\frac{a}{b}} = \frac{2b}{a} \] **Réponse :** \[ \frac{2b}{a} \] --- ### **(d)** \[ \cos\left(\arctan \frac{15}{8} - \arcsin \frac{7}{25}\right) \] **Solution :** 1. **Soit \(\alpha = \arctan\left(\frac{15}{8}\right)\) et \(\beta = \arcsin\left(\frac{7}{25}\right)\). Nous souhaitons calculer \(\cos(\alpha - \beta)\).** 2. **Déterminons les valeurs trigonométriques pour \(\alpha\) :** - \(\tan \alpha = \frac{15}{8}\), donc dans un triangle rectangle, les côtés opposé et adjacent sont 15 et 8 respectivement. - L'hypoténuse est \(\sqrt{15^2 + 8^2} = \sqrt{225 + 64} = \sqrt{289} = 17\). - Ainsi, \(\sin \alpha = \frac{15}{17}\) et \(\cos \alpha = \frac{8}{17}\). 3. **Déterminons les valeurs trigonométriques pour \(\beta\) :** - \(\sin \beta = \frac{7}{25}\), donc \(\cos \beta = \sqrt{1 - \sin^2 \beta} = \sqrt{1 - \frac{49}{625}} = \sqrt{\frac{576}{625}} = \frac{24}{25}\). 4. **Utilisons la formule de la différence des angles pour le cosinus :** \[ \cos(\alpha - \beta) = \cos \alpha \cos \beta + \sin \alpha \sin \beta \] \[ = \left(\frac{8}{17}\right) \left(\frac{24}{25}\right) + \left(\frac{15}{17}\right) \left(\frac{7}{25}\right) \] \[ = \frac{192}{425} + \frac{105}{425} = \frac{297}{425} \] **Réponse :** \[ \frac{297}{425} \] ---

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Extra Insights

To break down these expressions, let’s venture into some fun identities! First up, in part (a), recall that \( \cos \left( \frac{\pi}{2} - x \right) = \sin x \). Applying that gives us \( \frac{1}{2} - \sin \left(\frac{1}{2} \arcsin \frac{3}{5}\right) \). Remember, \( \sin \left( \arcsin y \right) = y \), and with some clever substitution, we can simplify this expression easily. Now onto part (b)! Here, \( \sin(2x) = 2 \sin x \cos x \) can help with the first term. Since \( \arctan \frac{3}{4} \) is your angle x, find \( \sin x \) and \( \cos x \) from the right triangle formed. Meanwhile, \( \tan \left( \frac{1}{2} \arcsin \frac{5}{13} \right) \) can be dealt with using the half-angle formula, giving you a clear path to evaluating the whole expression.

Related Questions

Latest Trigonometry Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy